The political economy of inflation - Frances Coppola (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
For the last 40 years, macroeconomics has been dominated by Milton Friedman's view that inflation occurs when the supply of money rises more quickly than economic output – 'too much money chasing too few goods', as the saying goes. If inflation is always due to an imbalance of money supply and output, central banks alone determine the path of inflation, and fiscal policy merely has a redistributive function. This paper draws on historical and empirical evidence as well as recent theoretical literature to show that this view is mistaken. Monetary policy has redistributive effects, and fiscal policy affects the money supply. It is therefore impossible to separate them in practice. Both fiscal and monetary policy have inflationary consequences, and because their distributional effects are different, monetary policy cannot fully offset fiscal decisions. Fiscal and monetary policy are influenced by political decisions and are themselves political in nature. Since inflation reflects spending and saving patterns which are affected by political choices, it is fundamentally a political phenomenon.
Keywords: E31; E4; E5; E6; P16; P44; 330; inflation; money supply; monetary policy; fiscal policy; politics